The Prospects for Customary Law in Transitional Justice: The Case of Fiji - Quinn, Joanna R. (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2019)
The use of customary law shows real promise in addressing the challenges that arise when confronting the legacies of past human rights abuses and atrocities.  Unlike typical transitional justice mechanisms like trials, truth commissions, and reparations programs, customary practices are community-based and well-known to the people who use them.  Indeed, customary practices could be used in transitional societies in place of “foreign” practices to bring about the same objectives.  This paper considers the role that customary law plays in Fiji.  It further assesses the prospects for the use of customary, traditional law in situations where transitional justice is called for.